2014
DOI: 10.1177/1464419314530696
|View full text |Cite
|
Sign up to set email alerts
|

Road profile effects on the performance and energy regeneration of the electromagnetic suspension system

Abstract: This paper deals with the electromagnetic damper, which is composed of a permanent-magnet DC motor, a ball screw and a nut, as the passive, semi-active and active actuator in the vehicle suspension system. The main objective pursued in the paper is to study the dependences of the performance and energy regeneration of the electromagnetic suspension system on the road unevenness and the travel speed. For this purpose, the nonlinear equations of the electromagnetic damper electric circuit in the three mentioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is found that ride comfort is one of the most common research contents of automobile performance. 2,3 According to the literature, the methods to optimise ride comfort can be divided into single-objective optimisation 4 and multi-objective optimisation. 5 Yu 6 pointed out three indexes of ride comfort: body acceleration, wheel dynamic load, and suspension dynamic travel.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that ride comfort is one of the most common research contents of automobile performance. 2,3 According to the literature, the methods to optimise ride comfort can be divided into single-objective optimisation 4 and multi-objective optimisation. 5 Yu 6 pointed out three indexes of ride comfort: body acceleration, wheel dynamic load, and suspension dynamic travel.…”
Section: Introductionmentioning
confidence: 99%
“…Even if a small amount of energy is saved or recovered, this helps to improve the efficiency of vehicles. 33 As is well known, the time delay is a characteristic which is commonly encountered in various engineering systems, such as pneumatic and hydraulic systems and industrial processes. 34,35 Even though the delay time may be short, it can nevertheless limit the control performance when delays appear in the feedback loop.…”
Section: Introductionmentioning
confidence: 99%